Karakteristik Sifat Fisik Membran Elektrolit Polimer Berbasis Kitosan Larva Black Soldier Fly/Polivinil Alkohol/Poliakrilonitril dengan Penambahan Ammonium Klorida - Muhammad Thoriq Al Fath; Dalimunthe, Nisaul Fadilah; Sidabutar, Rivaldi; Michael; Samosir, Rosma Natalia; Thiodorus Marvin Tjandra (Jurnal Teknik Kimia USU, 2024)
Black soldier fly larvae shells/BSF-based chitosan can be utilized as polymer electrolyte membrane. This research aims to analyze the physical characteristics of BSF chitosan/PVA/PAN/NH4Cl by varying amount of chitosan and ratio of PVA: PAN. Membrane was fabricated using the phase inversion method. Polymer electrolyte with a mixture of 1.20 g of PVA/PAN with ratio variations of 10:90 and 20:80 and chitosan variations of 2.4 g; 2.8 g; and 3.2 g. Chitosan was also FTIR-characterized. Density and wÃ¡ter absorption of polymer electrolyte with chitosan composition of 2.4 g; 2.8 g; 3.2 g and PVA/PAN ratio of 10:90 were 0.824 g/mL; 1 g/mL and 1.51 g/mL and water absorption 28.571%; 38.333%; and 46.154%, respectively; and at PVA/PAN ratio of 20:80 were 0.734 g/mL; 1.03 g/mL and 1.096 g/mL and water absorption 62.5%; 66.667% dan 100%, respectively. Best physical property was obtained with the incorporation of 2.4 g of chitosan and 10:90 PVA/PAN ratio.